(untitled) (Perioperaciina Medicina, 2024)
Cold urticaria (CU) is an allergic reaction that manifests itself as hives-like rashes or red spots in response to general or local cooling of the body. Th e disease can be acquired or hereditary, and in the cold season it can affect all segments of the population. Th is pathological condition, at first glance, does not seem to be a very dangerous variant of a local cold injury, but in persons who are prone to exposure to low temperatures, especially with a burdened cold history, it may be accompanied by chronicity of the process and complicated by neurovasculitis, obliterating endarteritis and secondary Raynaud’s syndrome, may decrease the quality of life of the victims and become a cause of disability. The pathophysiology of CU is largely unknown, but it is likely to be related to immunoglobulin E (IgE) and mast cell activation. Cooling has been reported to induce the release of neutrophilic and eosinophilic chemotactic factors, prostaglandin D2, and tumor necrosis factor (TNF-α). Less common immunologic fi ndings in patients with CU include cryoglobulinemia consisting of monoclonal IgG and mixed IgG/IgM and IgG/IgA cryoglobulin types. The mechanisms of development of CU are mainly determined by the formation of cryoglobulins (cold hemolysins) and subsequent degranulation of mast cells. Th e diagnosis of CU depends on the patient’s history and the results of cold provocation tests. Patients with CU are recommended first of all not to overcool, to take warm showers, to wear warm clothes and a hat, and not to consume cold food and drinks. Treatment options include second-generation H1 antihistamines and glucocorticosteroids. New promising option is omalizumab, a humanized monoclonal antibody derived from a recombinant DNA molecule that targets and selectively binds to circulating IgE and affects mast cells function. In patients with CU undergoing general anesthesia, premedication including antihistamines and corticosteroids is recommended, along with strict maintenance of perioperative normotermia.